High Performance VLSI Signal Processing: Innovative Architectures and Algorithms : Volume I - Algorithms and Architectures. Edited by K. J. Ray LIU and Kung YAO. IEEE Press. 1998. ISBN 0-7803-3468-X - Villagarcía Wanza, Horacio A. (2001)
The book intends to address the important aspects of high-performance signal processing with a focus on the recent development of VLSI technology for signal processing. The editors collect much of all the research efforts and findings that have made high performance implementation of signal processing possible in the last decade in two volumes.